Relationships of trait-like factors with intercultural communication competence: religiosity as a moderator - Nadeem, Muhammad Umar (2019)
Intercultural communication competence (ICC) is a need of today, for those who live in multicultural societies and have frequent interactions with culturally different individuals. Competency of individuals during intercultural interactions derives from several trait-like factors, which directly or indirectly influence their communication. Previous researchers have pointed out the need to address the factors of empathy and religion during intercultural encounters. Furthermore, it is strongly recommended to expand and retest the integrated model of intercultural communication competence (IMICC) among multiple cultural perspectives. For these reasons, this study adopted IMICC, expanded it with empathy and religiosity, and tested it on the non-Western context of Malaysia. The study analyzed the moderating effect of religiosity and mediating effects attitude toward other cultures and motivation to engage in intercultural communication on intercultural communication competence. The research employed a survey technique and collected data from 388 international students of Universiti Utara Malaysia (UUM). The theoretical model of the research was analyzed using Structural Equation Modelling (SEM/AMOS). The findings show empathy, sensation seeking, and attitude toward culture directly influenced intercultural communication competence. Findings also showed the relationship of moderating effect of religiosity and mediating effect of attitude toward other culture (ATOC) were empirically justified. Nevertheless, the mediating effect of motivation to engage towards empathy, sensation seeking, ethnocentrism and intercultural communication competence was not established in this regard. This study empirically justified the significant relationships of all research variables trait-like factors with Intercultural Communication Competence. The results are promising; however, it is the initial step toward the validation of an Integrated Model of Intercultural Communication Competence (IMICC) on the non-Western context. The research practically contributes the usage of the model to the policymakers in order to develop the training program for the students. Further refinement and retesting of the model are necessary for future studies.